PERAN PEKERJA PEREMPUAN SEBAGAI KEPALA RUMAH TANGGA DI WILAYAH JAKARTA TIMUR BERDASARKAN PRINSIP CEDAW: The Role of Female Workers as Heads of Households in East Jakarta Based on Cedaw Principles - Salsabillah Beby Pinkan Khoirunisah; Harto (Reformasi Hukum Trisakti, 2026)
Rising living costs and increasing prices in the modern era have compelled women to work harder to support their families’ economic needs. This phenomenon has led to a shift in women’s roles from the domestic sphere to the public domain, where they often assume responsibilities as heads of households. Based on this context, this study examines the role of female workers as heads of households from the perspective of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). This research employs a socio-legal approach, which views law not merely as written norms (law in the books), but as a social phenomenon operating in society (law in action), using both primary and secondary data, including primary to tertiary legal materials. The result and the conclusion indicate that although CEDAW provides a strong normative framework for ensuring gender equality and the protection of women workers’ rights, its implementation in Indonesia remains insufficient, particularly for women who perform dual roles as heads of households. Existing legal protection and labor policies have not yet fully responded to women’s socio-economic realities, highlighting the need to strengthen the implementation of CEDAW principles to achieve substantive gender equality